A complete course in engineering physics-II / Roy, Sudipta: S.Chand 2nd.ed. - Ghosh, T. and Biswas, D.
A complete course in engineering physics-II / Roy, Sudipta: S.Chand 530 R888v2 2nd.ed. No. of Copies : 2